Verksamhetsutveckling inom sluten psykiatrisk vård En fallstudie baserad på principer för Lean produktion och teorier om psykosocial arbetsmiljö - Andreasson, Viktoria; Pettersson Hagerfors, Pauline (My University, 2017)
E2017:077, The Swedish health care system is characterized by inadequate co-operation within healthcare chains. There is also an insufficient continuity in the follow-up of patients who are discharged from care units and health professionals experience both high physical and mental workloads. The turnover within the psychiatric specialist care is high, which complicates the work and degrades the care of mentally ill patients. In addition, mental illness has increased sharply in Sweden over the last ten years, an increase which seems likely to continue during the years to come. The study has been conducted at a psychiatric inpatient care unit for bipolar patients at Sahlgrenska University Hospital. The purpose of the study is to highlight the unit's strength and problem areas, as well as to present improvement suggestions and how they can be implemented. Through observations and interviews with health professionals at the unit, a current-situation analysis has been made. Improvement suggestions have also been developed based on Lean production and theories within psychosocial work environment. Subsequently, recommendations are presented regarding implementation of the suggested improvement based on Kotter's eight-step model. The health care unit is generally well functioning and characterized by a good work environment, good patient contingency, committed leadership and driven employees who are able to influence their work. In addition, the unit is at the leading edge of most performance measurements compared to other units at the clinic. Inadequate introduction of the assistant physicians and curator, high turnover of the assistant physicians and experienced high workload are some of the improvement areas identified at the unit. In addition, there are ambiguities about current routines and how they are communicated. Finally, the co-operation with the bipolar centre is deficient and the sitting round is very timeconsuming. The improvement suggestions includes a standardized introduction for all new employees, that the operation’s chief physician is involved in the recruitment process of the assistant physicians and in the unit's workplace meetings. It is also recommended that a full time curator should be employed at the unit, the 5S tool is proposed for routines, the fax system is suggested to be phased out and study visits should be done within the care chain. Finally, it is recommended that the unit acquires a digital screen for planned medical sessions for patients and a so-called patient-centered round should be implemented. The result from the study can provide a basis for the improvement work at other psychiatric units. Finally, the study presents recommendations on continued studies within the care chain, but also within the bipolar healthcare system in general. The report is written in Swedish.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics